2016
DOI: 10.5902/2179460x20381
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos De Uma Camada De Palha No Comportamento Térmico Do Solo

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…In the straw mulch layer, a depletion of heat flux also occurs due to its low heat conductivity, which reduced both soil heating (during the day) and cooling (during the night) in depth. These results are in alignment with those described by Webler et al (2016), indicating lower energy losses in covered soil.…”
Section: Alterações Da Temperatura Em Solo Coberto De Palha De Aveia-supporting
confidence: 92%
See 1 more Smart Citation
“…In the straw mulch layer, a depletion of heat flux also occurs due to its low heat conductivity, which reduced both soil heating (during the day) and cooling (during the night) in depth. These results are in alignment with those described by Webler et al (2016), indicating lower energy losses in covered soil.…”
Section: Alterações Da Temperatura Em Solo Coberto De Palha De Aveia-supporting
confidence: 92%
“…Straw mulch has been shown to reduce Ts (Silva et al, 2006;Webler et al, 2016) and thermal amplitude (Dahiya et al, 2007;Furlani et al, 2008;Coelho et al, 2013). Ramakrishna et al (2006) and Liu et al (2014) found that, during cold periods, Ts of covered soil is greater than that of bare soil; however, the inverse was observed during hot periods.…”
Section: Alterações Da Temperatura Em Solo Coberto De Palha De Aveia-mentioning
confidence: 99%